Upaya Guru dalam Mengatasi Masalah Permasalahan Pembelajaran IPS Pada Era Digital - Enjel Elfrida Purba; Nur Haliza; Jelita Maria Christine; Sayidah Latifah Hanum; Andi Taufiq Umar (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
In research focused on all social studies learning problems at the high school level, where these problems were found based on the journal "Finding social studies learning problems at all levels of formal education (elementary school, middle school, high school) several problems were found that were felt by high school students (SMA) such as teachers center, learning centered on textbooks, social studies learning which is considered second grade, and also technological developments. The research method used is a qualitative research method using subjects from SMA Negeri 1 Percut Sei Tuan and the data collection techniques used are interviews and documentation studies. The results obtained from this research are that the teacher concerned overcomes existing problems, namely by providing motivation and advice to his students. The advice given does not seem to be bringing down, but rather building. Apart from that, the teacher who was interested also made a few jokes while the lesson was taking place. Teachers also implement several rules in their classes, such as not being allowed to use cell phones during teaching and learning activities.